THE IMPACT OF FIELD STUDY ACTIVITIES ON TEACHING MODULE DEVELOPMENT AND TEACHER COMPETENCE - Siti Fatimah Hasibuan; Rosti Malini Gultom; Zainal Efendi Hasibuan (PT. Jurnal Center Indonesia Publisher, 2026)
Field study activities are an important part of experiential learning in teacher education. This study aims to examine the impact of field study activities on teaching module development and teacher competence. The research employed a qualitative descriptive approach involving graduate students and teachers participating in field study programs. Data were collected through observation, interviews, and document analysis of teaching modules. The findings indicate that field study activities positively influence the development of contextual teaching modules and enhance teachers’ pedagogical, professional, and social competences. The study concludes that field study activities support continuous professional development and improve instructional practices. These findings provide practical implications for teacher education programs.